Impact of Traumatic Dental Injuries on Oral Health-Related Quality of Life using the Adolescent Oro-Dental Trauma Impact Index among 8-12 year-old school children of Goa, India - Dorothy Cardozo; Elaine Savia Barretto; Dinesh Francis Swamy; Aswathy Sudarsanan (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Context: Traumatic dental injuries (TDIs) to permanent teeth are a significant public health concern due to their high prevalence and detrimental impact on a child’s overall development. In addition to physical distress, TDI can cause social and emotional disturbances leading to long-term challenges. Hence, TDI impact cannot be underestimated. Aims: The aim is to measure the impact of TDI on Oral Health-Related Quality of Life (OHRQoL) using the Adolescent Oro-Dental Trauma Impact Index (AODTII) among 8-12 year-old school children of Goa. Settings and Design: A cross-sectional study was conducted among 8-12 year-old school children of Goa. Materials and Methods: Multistage cluster sampling was carried out in 8-12 year-old school children of Goa. Random selection of one school per Taluka (12 Talukas) was done. A convenience sample of 202 children with a history of TDI from these selected schools was drawn and oral examination was carried out. The validated AODTI Index questionnaire was used to measure self-reported OHRQoL. Statistical Analysis: Descriptive data were depicted as frequencies and percentages. Pearson’s Chi-square test was used to obtain the impact significance of treated versus the nontreated TDIs and Independent sample t-test was used to compare the composite scores among treated and nontreated groups. Results: Among 202 sample children with TDI, 15.8% (32 children) had a significant impact on OHRQoL. Conclusions: The study highlights the profound and multifaceted impact of TDI on young children, consequently influencing their overall development. AODTII Index serves as a simple, reliable, and feasible instrument for evaluating TDI impact on OHRQoL.